Human Resource Management of Agrotourism-based BUMDes (Township and Village Enterprise) on Rural Community Empowerment - Vi’in Ayu Pertiwi; Destyana Ellingga Pratiwi; Deny Meitasari (Future Science, 2022)
Agrotourism has an important role in developing the economy and has been a source of job opportunities in the villages in Indonesia. Many BUMDes’ (Township and Village Enter-prises/TVEs) manage agrotourism as their core businesses. Meanwhile, most of them have experienced a turnover-declining during the Covid-19 pandemic and need new managerial strategies to survive this pandemic. Human resource holds a strategic function in this problem since most of the BUMDes recruits their employers locally since it is designed to reduce unemployment in the village while utilizing the resources possessed by their villages. Contrarily, the pandemic of Covid-19 has given a severe impact on agrotourism in Indonesia and has pushed BUMDes’ to cut their employer numbers for reasons of efficiency. This study aimed to describe the human resources management conducted by BUMDes during the Covid-19 Pandemic, employing a qualitative approach with the chairman and employees of BUMDes as the informants. Data from this research were analyzed by Miles and Huberman’s model. The research was held on agrotourism-based BUMDes in Malang and Batu. The results indicated that the BUMDes’ managers used the strategy of the temporary off-work system when the government implemented community activity restrictions (PPKM). During this off-work time, BUMDes did not pay their employees but gave a food package as social assistance to the workers. It proved that BUMDes was applying a social systems approach in managing their employees during the pandemic to hold its function as one of the economic pillars for villagers.